Enhancing Science Process Skills in Physics Education: The Impact of the Phyphox Smartphone Application in High School Laboratories - Evains, Andio Calen; Anggereni, Santih; Lanto, Muh. Said (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2023)
This study explores the effectiveness of smartphones as measurement tools in physics laboratories, focusing on the science process skills of Class XI students at SMA Negeri 1 Wajo. Employing a Pre-Experimental One-Shot Case Study design, we integrated the Phyphox application into the curriculum and analyzed its impact on students' scientific understanding. Our methodology included purposive sampling of 24 students and data collection via science process skill tests, lesson plans, and student worksheets. Descriptive and inferential statistical analyses revealed a significant improvement in students' science process skills, with an average score of 72.08. The one-sample t-test showed an essential value of 0.000, indicating a positive effect of the Phyphox application. These findings suggest a potential shift towards technologically integrated learning environments in physics education, enhancing student engagement and comprehension. While promising, the study acknowledges its sample size and context limitations, highlighting the need for further research in diverse educational settings. This study contributes to the growing body of research advocating digital tools in education, aiming to prepare students for a technologically advanced world.